Financial Performance of PT Pertamina Geothermal Energy Tbk Before and After the Disclosure of the Fuel Adulteration Case: A Comparative Analysis - Apni Yunikartika Putri; Darwis; Damirah; Ismayanti (Economics and Business Journal (ECBIS), 2026)
This study aims to analyze the differences in the financial performance of PT Pertamina Geothermal Energy Tbk before and after the disclosure of the fuel adulteration case involving its parent company. This research employs a quantitative comparative approach using quarterly financial statement data from 2024–2025. The analysis was conducted using descriptive statistics and the Wilcoxon Signed Rank Test. The results show that descriptively, most financial ratios experienced a decline, particularly in profitability and activity ratios, along with a decrease in liquidity and a slight increase in solvency. However, the Wilcoxon test results indicate that these changes are not statistically significant. These findings suggest that despite reputational pressure from the parent company’s crisis, the company’s financial performance remains relatively stable. The limited sample size is also considered a factor influencing the results